Increased Sympathetic Renal Innervation in Hemodialysis Patients Is the Anatomical Substrate of Sympathetic Hyperactivity in End‐Stage Renal Disease. Issue 12 (26th November 2015) - Mauriello, Alessandro; Rovella, Valentina; Anemona, Lucia; Servadei, Francesca; Giannini, Elena; Bove, Pierluigi; Anselmo, Alessandro; Melino, Gerry; Di Daniele, Nicola
Abstract : Background: Renal denervation represents an emerging treatment for resistant hypertension in patients with end‐stage renal disease, but data about the anatomic substrate of this treatment are lacking. Therefore, the aim of this study was to investigate the morphological basis of sympathetic hyperactivity in the setting of hemodialysis patients to identify an anatomical substrate that could warrant the use of this new therapeutic approach. Methods and Results: The distribution of sympathetic nerves was evaluated in the adventitia of 38 renal arteries that were collected at autopsy or during surgery from 25 patients: 9 with end‐stage renal disease on dialysis (DIAL group) and 16 age‐matched control nondialysis patients (CTRL group). Patients in the DIAL group showed a significant increase in nerve density in the internal area of the peri‐adventitial tissue (within the first 0.5 mm of the beginning of the adventitia) compared with the CTRL group (4.01±0.30 versus 2.87±0.28×mm 2, P =0.01). Regardless of dialysis, hypertensive patients with signs of severe arteriolar damage had a greater number of nerve endings in the most internal adventitia, and this number was significantly higher than in patients without hypertensive arteriolar damage (3.90±0.36 versus 2.87±0.41×mm 2, P =0.04), showing a correlation with hypertensive arteriolar damage rather than with hypertensive clinical history. Conclusions: The findings from this study provide a morphological basis underlying sympathetic hyperactivity in patients with end‐stage renal disease and might offer useful information to improve the use of renal denervation in this group of patients.